2012
DOI: 10.1038/clpt.2011.336
|View full text |Cite
|
Sign up to set email alerts
|

PPARA: A Novel Genetic Determinant of CYP3A4 In Vitro and In Vivo

Abstract: Interindividual variability in cytochrome P450 3A4 (CYP3A4) is believed to be largely heritable; however, predictive genetic factors have remained scarce. Using a candidate-gene approach in a human liver bank, we identified singlenucleotide polymorphisms (SNPs) in the Ah-receptor nuclear translocator (ARNT), glucocorticoid receptor (GR), progesterone receptor membrane component 2 (PGRMC2), and peroxisome proliferator-activated receptor-α (PPARA) that are associated with CYP3A4 phenotype. Validation in atorvast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 51 publications
4
127
2
Order By: Relevance
“…It can be hypothesised that the lack of effect in the current work may be due to the small sample size and the complete absence of homozygous variant individuals with respect to these SNPs (Table 2). Similarly, the effects of two other SNPs that have been of particular clinical interest recently, namely rs35599367 (CYP3A4) and rs4253728 (PPARA) [18,23,26], were not possible to be investigated in the current work as all studied individuals carried the homozygous wild-type genotype (Table 2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be hypothesised that the lack of effect in the current work may be due to the small sample size and the complete absence of homozygous variant individuals with respect to these SNPs (Table 2). Similarly, the effects of two other SNPs that have been of particular clinical interest recently, namely rs35599367 (CYP3A4) and rs4253728 (PPARA) [18,23,26], were not possible to be investigated in the current work as all studied individuals carried the homozygous wild-type genotype (Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…For the purpose of this work, all studied participants were retrospectively genotyped for 18 genetic polymorphisms located in 7 different genes. More specifically 3, 3, 1, 1, 7, 2 and 1 polymorphisms were genotyped in the ABCB1, ABCG2, CYP3A4, CYP3A5, SLCO1B1, SLCO2B1 and PPARA genes respectively, as previous literature suggests that all these genes might be implicated in atorvastatin disposition [14,15,[22][23][24][25][26]. The distribution of these variants in the studied population is reported in Table 2.…”
Section: Description Of the Available Data For Model Developmentmentioning
confidence: 99%
“…These results are in concordance with the reduced CYP3A4 protein/activity levels previously observed in vitro. [54] At present, PPARA c.208+3819A>G appears to be the PPARA sequence variant with the strongest influence on Tac pharmacokinetics but this observation requires confirmation.…”
Section: Ppar-α and Pxrmentioning
confidence: 99%
“…In vitro, PPARA c.209-1003G>A and c.208+3819A>G were associated with reduced expression of PPAR-α, and consistently related to lower CYP3A4 mRNA levels, protein expression, and enzymatic activity. [54] Recently, Lunde et al found that expression of at least one PPARA variant allele was significantly associated with a higher Tac C 0 /D ratio, when adjusting for POR*28, CYP3A5*3, and CYP3A4*22 among 229 kidney transplant recipients. [48] A detailed analysis of the two PPARA sequence variants showed significantly increased Tac exposure in patients homozygous for PPARA-α c.209-1003G>A.…”
Section: Ppar-α and Pxrmentioning
confidence: 99%
“…Adding to uncertainty, the length of this hypervariable period varies from one enzyme to another (Hines, 2008). Although these hypervariable windows likely are linked to variability in the molecular mechanisms controlling enzyme ontogeny (Schuetz, 2004;Perera et al, 2009;Klein et al, 2012), those regulatory mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%